2019
DOI: 10.3389/fmars.2019.00658
|View full text |Cite
|
Sign up to set email alerts
|

Testing Industrial-Scale Coral Restoration Techniques: Harvesting and Culturing Wild Coral-Spawn Slicks

Abstract: Accelerating the recovery of marine coastal ecosystems is a global challenge that has been attempted on many systems around the world. Restoration efforts have shown varying levels of success at localized-scales, but developing techniques for large-scale application are still in their nascent stage for many systems. For seagrass meadows and marsh plants, large-scale successes have been realized by distributing seeds from moving boats or planes, respectively. Similarly for coral reefs, the harvesting, culturing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…Other examples for biotic motivations are an increase in the number of native species (e.g., for saltmarsh), habitat creation, ecosystem connectivity, and increasing the ecological resilience of the ecosystem (Table S1). Improving the approach to restore coral reefs by harvesting and culturing wild coralspawn slicks to apply at large, industrial scales (Doropoulos et al, 2019) is an experimental (or heuristic) motivation. Building community awareness, involvement, a shared responsibility for the restoration site, and creating jobs through restoration activities is an idealistic motivation for the restoration of coral reefs (Kittinger et al, 2016).…”
Section: Motivations For Engaging In Marine Coastal Restorationmentioning
confidence: 99%
“…Other examples for biotic motivations are an increase in the number of native species (e.g., for saltmarsh), habitat creation, ecosystem connectivity, and increasing the ecological resilience of the ecosystem (Table S1). Improving the approach to restore coral reefs by harvesting and culturing wild coralspawn slicks to apply at large, industrial scales (Doropoulos et al, 2019) is an experimental (or heuristic) motivation. Building community awareness, involvement, a shared responsibility for the restoration site, and creating jobs through restoration activities is an idealistic motivation for the restoration of coral reefs (Kittinger et al, 2016).…”
Section: Motivations For Engaging In Marine Coastal Restorationmentioning
confidence: 99%
“…Demographic modeling suggests that restoration of up to 10 5 adult colonies is feasible by harvesting wild coral-spawn slicks and developing these in large vessels, with minimal impact to wild populations (Doropoulos et al, 2019a). An initial pilot study on the Great Barrier Reef (Australia) yielded 400 times more larvae than predicted by a model (Doropoulos et al, 2019b), due to much greater densities of gametes found in coral spawn-slicks than previously recorded in the literature, and higher survival rates of gametes than anticipated.…”
Section: Coral Reefsmentioning
confidence: 79%
“…Most coral taxa (63%) are hermaphroditic spawners (Baird et al, 2009). Restoration methods that harness their immense supply of propagules has been conceptualized for decades (Rinkevich, 1995 ; Figures 2e,f) but is challenging in practice because they release gametes only once or twice a year (Babcock et al, 1986), the formation of aggregations of spawn depends on local weather and currents (Oliver and Willis, 1987), and mortality of coral spawn is high (Pollock et al, 2017;Doropoulos et al, 2019b). In some experiments that have sought to overcome these constraints, spawn were collected and reared to larvae in situ in floating ponds; larvae were then pumped directly from these ponds into enclosures attached to the reef or settled onto biologically conditioned artificial substrata such as tiles or aragonite plugs, which are placed onto reefs or back into nurseries for continual production (Heyward et al, 2002;Omori and Iwao, 2014;Omori, 2019).…”
Section: Coral Reefsmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach aims to increase recruitment rates, coral cover [17], and genetic diversity that may improve coral adaptive and evolutionary potential, and increase resilience in depleted coral populations [18][19][20]. Using this approach, millions of sexually derived coral larvae can be sourced from sexually mature coral colonies from ex situ spawning in a controlled hatchery facility [21,22], or in situ by using spawn collectors placed on top of individual corals [23], or from natural coral spawn slicks [24][25][26]. Typically, competent larvae are then settled on artificial substrata and kept in land-or ocean-based nurseries before they are outplanted on the reef [5].…”
Section: Introductionmentioning
confidence: 99%